GIS mapping of biogas potential from animal wastes in Bursa, Turkey - Ozsoy, Gokhan; Alibas, Ilknur (International Journal of Agricultural and Biological Engineering, 2015)
This paper introduces biogas potential of animal waste in Bursa, an important agricultural, industrial and tourism centre in northwest Turkey. This research has focused on Bursa’s biogas potential from animal wastes. The potential quantity of electric energy, the potential amount of biogas as well as potential bio-electric energy per capita to be obtained from animal wastes were studied. If the evaluation of biogas potential is conducted thoroughly, 1.12% of the electricity consumption of Bursa can be met with the conversion of biogas from animal wastes into electricity. This study also revealed that the power for 95% of street lighting, approximately twofold of the electricity consumed in official apartments and all of the agricultural irrigation operations can be provided with electrical energy obtained from biogas obtained from animal wastes in Bursa. In addition, the research efficiency was improved by creating thematic maps in GIS, which enabled differences in data among the districts to be observed more clearly.DOI: 10.3965/j.ijabe.20150801.010Citation: Ozsoy G, Alibas I. GIS mapping of biogas potential from animal wastes in Bursa, Turkey. Int J Agric & Biol Eng, 2015; 8(1): 74-83.